Desenvolvimento profissional de formadores de professores de matemática que são Investigadores da docência - Coura, Flávia Cristina Figueiredo (Universidade Federal de São Carlos, 2018)
This study aims to understand the experiences of the professional development of Mathematics teacher educators who are researchers of teaching. The term “Mathematics teacher educators” refers to Superior Education professionals who work with the training of Mathematics teachers, while “researchers of teaching” refers to those who are committed to the training of teachers and to teaching itself, from which they conduct their investigations and produce knowledge-of-practice offering support to their own and other’s professional practices. The present research was developed based on Clandinin and Connelly observations regarding narrative inquiry. The data was produced from dialogical in-depth interviews with a biographical-narrative aspect performed individually with each of the six participants. The field texts, i.e., the mapping of the trajectory of the educator, the transcription of the interview, and the field notes, were produced by the doctoral candidate from, respectively, the academic production of each participant, the transcription of the individual interviews, and the notes about the conduction of these interviews. The transition from the field texts to the research texts resulted in six narratives that reveal the experiences of the professional development of the Mathematics teacher educators who are researchers of teaching. From the narratives of each participant, a chronology of the important elements could be established and, therefore, it was possible to identify the professional development experiences had by such educators: a relationship of proximity and interaction with the school and with the teacher who teaches Mathematics in Basic Education; the identification/distinction of a particular mathematics for the work of the teacher; the valuing of a mathematical knowledge for the training of the teacher who teaches Mathematics, to be addressed with the other knowledge from the Knowledge Base for Teaching; the constitution of a training practice towards the professional activity of the teacher who teaches Mathematics and the search of theoretical and empirical support to understand and guide this professional activity. The transversal analysis of the narratives aimed to follow the diachronic movement of the experiences present in the participants’ narratives organized in three moments/movements in order to highlight the transformations in the stories of both their lives and their formation while they were constituting themselves as (1) Mathematics teachers, (2) Mathematics teacher educators, and (3) researchers of teaching; this allowed for the understanding of how Mathematics teacher educators who are researchers of teaching developed themselves professionally. These transformations were marked by shifts in the position of the educators in relation to the knowledges pertaining to their professional activity: in order to constitute themselves as Mathematics teachers, they produced knowledge-in-practice of teaching Mathematics; in order to constitute themselves as teacher educators, they produced knowledge-in-practice of training teachers; and, in order to constitute themselves as researchers of teaching, they produced knowledge-of-practice of teaching Mathematics and of training teachers. In these movements, the way in which the participants developed themselves professionally is strongly related both to the commitment they established with their teaching activity, as well as to the interaction they built between researching and teaching, from the time they taught Mathematics onwards.
Professional development of mathematics teacher educators who are researchers of teaching
Keywords: Formador de professores de matemática; Desenvolvimento profissional; Formação de professores de matemática; Pesquisa narrativa; Mathematics teacher educators; Professional development; Mathematics teacher education; Narrative inquiry; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO